Characterisation of protein-truncating and missense variants in PALB2 in 15 768 women from Malaysia and Singapore. Issue 5 (2nd April 2021) - Ng, Pei Sze; Boonen, Rick ACM; Wijaya, Eldarina; Chong, Chan Eng; Sharma, Milan; Knaup, Sabine; Mariapun, Shivaani; Ho, Weang Kee; Lim, Joanna; Yoon, Sook-Yee; Mohd Taib, Nur Aishah; See, Mee Hoong; et al.
Abstract : Background: Rare protein-truncating variants (PTVs) in partner and localiser of BRCA2 ( PALB2 ) confer increased risk to breast cancer, but relatively few studies have reported the prevalence in South-East Asian populations. Here, we describe the prevalence of rare variants in PALB2 in a population-based study of 7840 breast cancer cases and 7928 healthy Chinese, Malay and Indian women from Malaysia and Singapore, and describe the functional impact of germline missense variants identified in this population. Methods: Mutation testing was performed on germline DNA (n=15 768) using targeted sequencing panels. The functional impact of missense variants was tested in mouse embryonic stem cell based functional assays. Results: PTVs in PALB2 were found in 0.73% of breast cancer patients and 0.14% of healthy individuals (OR=5.44; 95% CI 2.85 to 10.39, p<0.0001). In contrast, rare missense variants in PALB2 were not associated with increased risk of breast cancer. Whereas PTVs were associated with later stage of presentation and higher-grade tumours, no significant association was observed with missense variants in PALB2 . However, two novel rare missense variants (p.L1027R and p.G1043V) produced unstable proteins and resulted in a decrease in homologous recombination-mediated repair of DNA double-strand breaks. Conclusion: Despite genetic and lifestyle differences between Asian and other populations, the population prevalence of PALB2 PTVs and associated relative risk of breast cancer, are similar to those reported in European populations.